2013
DOI: 10.1007/s10439-013-0817-3
|View full text |Cite
|
Sign up to set email alerts
|

High Sensitivity Micro-Elastometry: Applications in Blood Coagulopathy

Abstract: Highly sensitive methods for the assessment of clot structure can aid in our understanding of coagulation disorders and their risk factors. Rapid and simple clot diagnostic systems are also needed for directing treatment in a broad spectrum of cardiovascular diseases. Here we demonstrate a method for micro-elastometry, named Resonant Acoustic Spectroscopy with Optical Vibrometry (RASOV), which measures the clot elastic modulus (CEM) from the intrinsic resonant frequency of a clot inside a microwell. We observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 26 publications
2
27
0
Order By: Relevance
“…Atomic force microscopy-based micro- and nanorheology allows for precise measurements of the clot viscoelastic properties using a very small sample volume in the 3-50 nN force range [25, 26]. Another method named resonant acoustic spectroscopy with optical vibrometry measures the clot elastic modulus from the intrinsic resonant frequency of a clot [27]. Fibrin stiffness can be also measured using magnetic tweezers based on mechanical manipulation of magnetic beads embedded into the network [28-30].…”
Section: Viscoelastic Properties Of Fibrin (Fibrin Rheology)mentioning
confidence: 99%
“…Atomic force microscopy-based micro- and nanorheology allows for precise measurements of the clot viscoelastic properties using a very small sample volume in the 3-50 nN force range [25, 26]. Another method named resonant acoustic spectroscopy with optical vibrometry measures the clot elastic modulus from the intrinsic resonant frequency of a clot [27]. Fibrin stiffness can be also measured using magnetic tweezers based on mechanical manipulation of magnetic beads embedded into the network [28-30].…”
Section: Viscoelastic Properties Of Fibrin (Fibrin Rheology)mentioning
confidence: 99%
“…Their study showed that the system is sensitive to various fibrinogen contents and is capable to assess different CEM of purified clots formed with varying amounts of fibrinogen and thrombin. On the one hand, the RASOV has the potential to analyse the clot structure, composition and its functional mechanical properties, but on the other hand it is not able to measure coagulation dynamics like the oscillatory rheometer in this study [27].…”
Section: Discussionmentioning
confidence: 99%
“…One example of a novel clotting measurement was reported by Gongting et al [27]. The resonant acoustic spectroscopy with optical vibrometry (RASOV) measures the clot elastic modulus (CEM in kPa) via acoustic spectroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…While MM-OCT relies on the dynamic modulation of MNPs for image contrast, MM-OCE extracts the motion characteristics of the medium surrounding the MNPs in order to assess its biomechanical properties [1]. In MM-OCE, MNPs [1, 71-74] or magnetic microbeads [80, 81] can respond to a magnetic field and serve as force transducers. MNPs have negligible inertia compared to biological tissues, and hence the responsive motion reflects the viscoelasticity of the surrounding tissue in which the MNPs are embedded [49].…”
Section: Magnetomotive Nanoparticle Applicationsmentioning
confidence: 99%